Direct Production of Higher Oxygenates by Syngas Conversion over a Multifunctional Catalyst. (28th February 2019) - Lin, Tiejun; Qi, Xingzhen; Wang, Xinxing; Xia, Lin; Wang, Caiqi; Yu, Fei; Wang, Hui; Li, Shenggang; Zhong, Liangshu; Sun, Yuhan
Abstract: Selective synthesis of higher oxygenates (linear α‐alcohols and α‐aldehydes, C 2 + OH) from syngas is highly attractive but remains challenging owing to the low C 2 + OH selectivity and low catalytic stability. Herein we introduce a multifunctional catalyst composed of CoMn and CuZnAlZr oxides that dramatically increased the oxygenates selectivity to 58.1 wt %, where more than 92.0 wt % of the produced oxygenates are C 2 + OH. Notably, the total selectivity to value‐added chemicals including oxygenates and olefins reached 80.6 wt % at CO conversion of 29.0 % with high stability. The appropriate component proximity can effectively suppress the formation of the undesired C1 products, and the selectively propulsion of reaction network by synergetic effect of different components contributes to the enhanced selectivity to higher oxygenates. This work provides an alternative strategy for the rational design of new catalysts for direct conversion of syngas into higher oxygenates with co‐production of olefins. Abstract : Ein stabiler multifunktionaler Katalysator aus CoMn‐Oxiden und CuZnAlZr‐Oxiden katalysiert die direkte Umwandlung von Synthesegas in höhere Oxygenate und Olefine mit einer Gesamtselektivität von 80.6 Gew.‐% bei einer CO‐Konvertierung von 29.0 %. Die Synergie der beiden Komponenten spielt eine entscheidende Rolle, um die Bildung von C1 ‐Produkten zu unterdrücken und die Selektivität für höhere Oxygenate zu erhöhen.